Kontribusi Metode Latihan Shuttle Run terhadap Tendangan Mawashi Geri dalam Karate Dojo Inkai Sidoharo Sragen - Wirawan, Bayu; Setiawan, Ipang (Universitas Negeri Semarang, 2023)
The kick in karate is an effective attack in taking points from the opponent but has a fairly high level of difficulty, so it takes physical conditions that support so that the kick can be done well. The purpose of this study was to determine the effect of physical exercise, especially the legs using the shuttle run on the mawashi geri kick in the karateka Dojo Inkai Sidoharjo in Sragen Regency. The type of research used is experimental research, which is a type of research that aims to determine the specific effect of intentional treatment. Experiments in this study are pre-experimental types of pretest and posttest in one group. The data collection technique was carried out by non-probability porpose sampling with as many as 20 karateka. by testing as many mawashi kicks as possible in 10 seconds which is then processed using spss 25.The results of the shuttle run exercise have an effect but are not significant and increase 1,6% for male and 2,4% for female karateka after doing the exercise for 12 meetings